Exploration of Constructing a Team of Interdisciplinary Talents for Participatory Qinqiang in the New Era - Yang, Nan; Hong, Ji-myeong (Journal of Educational Research and Policies, 2024)
The inheritance and dissemination of traditional Qinqiang in the new era is facing the innovation of technology and the great changes in creative concepts. Combining the principles of communication, focusing on the construction of talent teams for the development of Qinqiang, changing people's stereotypical prejudices about the dissemination and inheritance of traditional opera art, changing the mimetic environment of its dissemination, creating a unique immersive viewing habit with a sense of atmosphere, retaining old audiences, and attracting new audiences. Taking the social factors of art development in the new era as an opportunity, focusing on the factors related to the development of Qinqiang, focusing on the technical means as the factor of communication, stimulating the audience's aesthetic interest in all aspects and dimensions, combining the new path of digital art inheritance and communication, and enriching the construction of a new generation of composite talents in Qinqiang.